2010
DOI: 10.2754/avb201079020233
|View full text |Cite
|
Sign up to set email alerts
|

Na+/K+ATPase Activity in Sheep with Natural Babesiosis

Abstract: The aim of this study was to determine the Na + /K + ATPase activity in the erythrocytes of sheep naturally infected with Babesia ovis before and after treatment. Seven diseased sheep and seven control animals were used for the study. Babesia infection was confirmed with Giemsa's staining of blood smears. Na

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…2) A decline in Na + /K + ATPase activity in the cell membrane. PachccoRosado et al 25 and Carageorgiou et al 26 described a decrease in hippocampus Na + /K + ATPase activity in hypothyroid rats and Yur et al 2 reported Na + /K + ATPase activity decreases in sheep naturally infected with babesiosis. It is likely that decreased levels of Na + /K + ATPase activity would have been observed in the animals studied here, eventually resulting in lipid peroxidation via unknown mechanism(s).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2) A decline in Na + /K + ATPase activity in the cell membrane. PachccoRosado et al 25 and Carageorgiou et al 26 described a decrease in hippocampus Na + /K + ATPase activity in hypothyroid rats and Yur et al 2 reported Na + /K + ATPase activity decreases in sheep naturally infected with babesiosis. It is likely that decreased levels of Na + /K + ATPase activity would have been observed in the animals studied here, eventually resulting in lipid peroxidation via unknown mechanism(s).…”
Section: Discussionmentioning
confidence: 99%
“… İletişim (Correspondence)  +98 441 3476434  kn_az@yahoo.com which is characterized by fever, anemia, icterus and hemoglobinuria 1,2 . B. ovis has been observed in most regions of Iran 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Babesia ovis induces the expression of severe pathogenic traits in sheep and causes sheep babesiosis, which is characterized by fever, anemia, icterus and hemoglobinuria (1,2). B. ovis has been observed in most regions of Iran (1).…”
Section: Introductionmentioning
confidence: 99%
“…Two species, Babesia ovis and Babesia sp. Xinjiang, are highly pathogenic, especially in sheep, and cause severe infections characterized by fever, anemia, icterus, and hemoglobinuria (1)(2)(3)(4). Babesia species can cause severe economic losses in sheep and goats, particularly in tropical and subtropical climates.…”
Section: Introductionmentioning
confidence: 99%
“…Intraerythrocytic parasites, such as Babesia and Plasmodium, are thought to produce hemolytic effects by oxidative stress and increased lipid peroxidation. Invasions of parasites demolish hematopoiesis and thus cause anemia (2,6), which is defined as a reduction in the number of erythrocytes and/ or a subnormal concentration of hemoglobin per unit volume of blood. The decrease in red cell mass results in reduced oxygen transport and may lead to tissue hypoxia and hemodynamic and nonhemodynamic compensatory events.…”
Section: Introductionmentioning
confidence: 99%